Formulation, Characterization, and Stability Assessment of a Novel Tobramycin-Loaded in Situ Gelling System for Enhanced Ocular Drug Retention - Darode, Arti Jivan, P. Parameswari, P. Parameswari; Shaikh, Darakhshan Afreen; Arora, Pooja; Das, Sukamal; Solanki, Sonal Nikunj; maratha, Sushma; Attri, Kavita (Journal of Neonatal Surgery, 2025)
This study aimed to develop and evaluate an in situ gelling ophthalmic formulation of Tobramycin for sustained drug release and enhanced ocular retention. The formulations were prepared using sodium alginate as a gelling agent and HPMC E50 LV or HPMC K4M as viscosity enhancers. The cold dispersion method was employed, and formulations were evaluated for clarity, pH, drug content, gelling capacity, viscosity, in vitro drug release, antimicrobial activity, ocular irritation, and stability. The formulations were clear and transparent, with a pH range of 6.48–6.52, ensuring ocular compatibility. Immediate gelation upon contact with simulated tear fluid led to controlled drug release over 10 hours, with IGF6 exhibiting the most sustained release. Rheological studies confirmed shear-thinning behaviour, allowing easy instillation and prolonged retention. Antimicrobial activity was comparable to the pure drug, ensuring effective bacterial inhibition. Ocular irritation studies in albino rabbits showed no signs of irritation or adverse effects, confirming safety for ophthalmic use. Accelerated stability studies demonstrated that IGF6 remained stable for one month with no significant changes in clarity, pH, viscosity, drug content, or release profile. The study concludes that Tobramycin-loaded in situ gelling formulations offer prolonged ocular retention, sustained drug release, and improved patient compliance. The optimized formulation (IGF6) showed superior stability and efficacy, making it a potential alternative to conventional eye drops for bacterial eye infections.